1967
DOI: 10.1111/j.1365-2621.1967.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Mortem Changes in Protein Extractability in Beef, Pork, and Chicken Muscle

Abstract: SUMMARY— The extractability of beef, pork, and chicken muscle with post‐mortem aging was studied. There was a general increase in viscosity and nitrogen content of the extracts with aging. Extractability of nitrogen and actomyosin reached a maximum at 2 weeks in both beef and pork. In chicken, maximum nitrogen and actomyosin extractability occurred at 4 and 6 days, respectively. Thus, in pork as well as in beef, two weeks' aging apparently are required to complete postmortem changes in muscle protein. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1967
1967
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…After a certain minimal level of actomyosin is reached, there is roughly a linear correlation between actomyosin content and emptying. The yield of actomyosin was similar to that found by other workers using this method (13), and recovery of protein from the various fractions was 100 5%. Since the actomyosin determinations were performed under an entirely different set of extracting conditions than the emptying, the two sets of data do not merely reflect two measures of the same phenomenon.…”
supporting
confidence: 87%
“…After a certain minimal level of actomyosin is reached, there is roughly a linear correlation between actomyosin content and emptying. The yield of actomyosin was similar to that found by other workers using this method (13), and recovery of protein from the various fractions was 100 5%. Since the actomyosin determinations were performed under an entirely different set of extracting conditions than the emptying, the two sets of data do not merely reflect two measures of the same phenomenon.…”
supporting
confidence: 87%
“…It has been shown that sarcoplasmic proteins d o not undergo large changes in compoosition during postmortem storage at 5 C or lower (Aberle and Merkel, 1966;Lawrie et al, 1963;Scopes, 1964). The extractability of the myofibrillar proteins has been shown t o increase up to 2 wk postmortem (Aberle and Merkel, 1966;McIntosh, 1967). Davey and Gilbert (1968a) reported an increase in the myofibrillar protein extract during aging of beef and rabbit muscle.…”
Section: Introductionmentioning
confidence: 99%
“…An early survey showed no gross changes in total mucoprotein hexosamine (McIntosh, 1961), collagen, elastin, or total nitrogen. Failure to find changes in total amount of connective-tissue components supported the view that the visual changes observed might be a reflection of much more subtle changes, probably structural in nature.…”
Section: -Journalmentioning
confidence: 96%
“…At the end of the designated aging period, these muscles were also wrapped and frozen. Later, the frozen muscles were thawed, and the mucoprotein fraction was isolated essentially as described earlier (McIntosh, 1965) except that precipitation by aminoacridine hydrochloride was conducted at pH 7 in an attempt to minimize protein degradation. With this modification, the resultant products had higher viscosity and lower hexosamine content than those found previously (McIntosh, 1966).…”
Section: Meat Samplesmentioning
confidence: 99%
See 1 more Smart Citation